Single-cell sequencing of the small and AT-skewed genome of malaria parasites - Shiwei Liu; Adam C. Huckaby; Audrey C. Brown; Christopher C. Moore; Ian Burbulis; Michael J. McConnell; Jennifer L. Güler (Genome Medicine, 2021)
Abstract Single-cell genomics is a rapidly advancing field; however, most techniques are designed for mammalian cells. We present a single-cell sequencing pipeline for an intracellular parasite, Plasmodium falciparum, with a small genome of extreme base content. Through optimization of a quasi-linear amplification method, we target the parasite genome over contaminants and generate coverage levels allowing detection of minor genetic variants. This work, as well as efforts that build on these findings, will enable detection of parasite heterogeneity contributing to P. falciparum adaptation. Furthermore, this study provides a framework for optimizing single-cell amplification and variant analysis in challenging genomes.